Variant-dependent oxidative and cytokine responses of human neutrophils to SARS-CoV-2 spike protein and anti-spike IgG1 antibodies - Almeida, Nathalie Bonatti Franco; Fantone, Kayla Marie; Sarr, Demba; Ashtiwi, Nuha Milad; Channell, Sarah; Grenfell, Rafaella Fortini Queiroz; Martins-Filho, Olindo Assis; Rada, Balázs (Frontiers in Immunology, 2023)
Introduction Severe forms of COVID-19, the disease caused by SARS-CoV-2, are characterized by acute respiratory distress syndrome, robust lung inflammation and death in some patients. Strong evidence has been accumulating that polymorphonuclear neutrophilic granulocytes (PMN) play an important role in the pathophysiology of severe COVID-19. SARS-CoV-2 directly induces in vitro PMN activation, mainly the release of neutrophil extracellular traps (NETs). However, the viral components inducing this PMN response remain unclear. Methods In this work human PMN responses were assessed in vitro in response to the spike (S) protein of two different SARS-CoV-2 variants, anti-S IgG1 antibodies or immune complexes formed by them. Production of reactive oxygen species (ROS) was measured by Diogenes-based chemiluminescence. Release of myeloperoxidase (MPO) was assessed by ELISA while secretion of a list of cytokines and growth factors was determined by high-performance multiplex cytokine assay. Results and discussion We show that the SARS-CoV-2 Omicron variant S protein and anti-spike IgG1, either alone or together, stimulate ROS production in human PMNs. We also observed that the SARS-CoV-2 Wuhan S protein and anti-S IgG1 antibody together trigger MPO release from PMNs. Based on the relevance of SARS-CoV-2 and influenza co-infections, we have also investigated the impact of influenza virus infection on the previous PMN responses to S proteins or anti-S antibodies. We did not detect any significant effect of influenza co-infection on ROS generation in PMNs. Our data also show that PMN stimulation by S proteins induced the release of different chemokines, growth factors, regulatory and proinflammatory cytokines. Overall, our findings show that the SARS-CoV-2 S protein, an anti-spike IgG1 antibody or their immune complex, promote oxidative responses of PMNs in a variant-dependent manner, contributing to a better understanding of the role of PMN responses during SARS-CoV-2 infection.